Social Ideal and its Implementation in the Philosophy of S. L. Frank - BUJOR, Evgenia; PROSEKOV, Sergey; SEREGINA, Tatyana; SHEVCHENKO, Olga; DYAGILEV, Vasily (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The paper examines the social philosophy of a prominent Russian thinker, Semen Frank with the aim of identifying its relations with general philosophical ideas, as well as with religious foundations of his thought. For these purposes, authors examine the basic concepts of Frank’s social philosophy in their interaction and connection. Based on the research, authors conclude that Frank built his social theory on the basis of the philosophy all-unity that gives primacy to the spiritual aspects of the social body over the material and empirical ones. The basic social concepts he develops are related with the two fundamental modes of the reality – ideal and empirical.RESUMEN El artículo examina la filosofía social de un destacado pensador ruso, Semen Frank, con el objetivo de identificar sus relaciones con ideas filosóficas generales, así como con los fundamentos religiosos de su pensamiento. Para estos fines, los autores examinan los conceptos básicos de la filosofía social de Frank en su interacción y conexión. Con base en la investigación, los autores concluyen que Frank construyó su teoría social sobre la base de la filosofía de la unidad total que da primacía a los aspectos espirituales del cuerpo social sobre bases materiales y empíricas. Los conceptos sociales básicos que desarrolla están relacionados con los dos modos fundamentales de la realidad: ideal y empírico.